Medical examination within the Reform of the Italian Public Administration - Grandi, Barbara; Petrone, Alfredo (Advances in Social Sciences Research Journal, 2015)
The Italian Reform of the Public Administration (art. 17 Act n. 124/2015) is opening to the opportunity to re-define the employment relation of the medical examiners – those in charge for controlling over the state of health anyone entitled to sick pay and other social-health-related rights, as well as disability-rights – by means of an agreed Convention with the National Institute for Pensions and Social Security (INPS).